2008
DOI: 10.1111/j.1752-7325.2007.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Overview and Quality Assurance for the Oral Health Component of the National Health and Nutrition Examination Survey (NHANES), 2003‐04

Abstract: The 2003-04 National Health and Nutrition Examination Survey (NHANES) was a collaborative effort involving 28 federal funding partners with the National Center for Health Statistics. The collaborators for the 2003-04 NHANES oral health component included the National Institute of Dental and Craniofacial Research and the National Center for Chronic Disease Prevention and Health Promotion, Division of Oral Health. Oral health data are available on 8272 persons aged 2 years or older. This report provides an overv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 19 publications
1
108
0
Order By: Relevance
“…In the oral environment, strontium and other divalent cations with a similar charge-to-size ratio to calcium can readily substitute in the lattice of hydroxyapatite. Dedhiya et al confirmed a calcium strontium apatite Ca 6 Sr 4 (PO 4 ) 6 (OH) 2 is formed by the substitution of intracrystalline calcium in apatite by strontium [18]. Gedalia et al reported a significant increase of radiodensity after immersing sound and etched dentin in a 25% (w/w) strontium chloride solution for 24 h. Increased radiodensity was due to formation of Ca-Sr apatite [15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the oral environment, strontium and other divalent cations with a similar charge-to-size ratio to calcium can readily substitute in the lattice of hydroxyapatite. Dedhiya et al confirmed a calcium strontium apatite Ca 6 Sr 4 (PO 4 ) 6 (OH) 2 is formed by the substitution of intracrystalline calcium in apatite by strontium [18]. Gedalia et al reported a significant increase of radiodensity after immersing sound and etched dentin in a 25% (w/w) strontium chloride solution for 24 h. Increased radiodensity was due to formation of Ca-Sr apatite [15].…”
Section: Introductionmentioning
confidence: 98%
“…The Centers for Disease Control and Prevention (CDC) first added tooth wear as a part of the National Health and Nutrition Examination Survey (NHANES) in 2003-2004 [6]. Physical structure loss of the enamel, cementum or surrounding soft tissue will lead to exposed dentin.…”
Section: Introductionmentioning
confidence: 99%
“…A third probing site (disto-facial) was added in 2001; however, information obtained only from measuring the mesio-facial and mid-facial sites are used in this report to be consistent with periodontal measurements collected prior to 2001. Detailed information on the NHANES dental examinations for the survey periods are available elsewhere (4,7,8). Table 3 shows the demographic distribution of sampled persons participating in the interview, MEC and oral health exam during 1988-1994 and 1999-2004.…”
Section: Oral Health Componentmentioning
confidence: 99%
“…Partial-mouth examinations, like the examination procedures used on NHANES, also may underestimate the prevalence of periodontal disease, particularly the more severe conditions (18-21). Nevertheless, information collected from current NHANES periodontal examination methods are useful for assessing trends in periodontal status in the United States (8).…”
Section: Seniors (65 Years and Older)mentioning
confidence: 99%
“…The World Health Organization introduced the Community Periodontal Index of Treatment Needs (CPITN) in 1987, recommending the use of pocket depth (PD) as a criterion for identifying cases of SP (World Health Organization, 1987). Influential oral health surveys, such the 2009 Adult Dental Health Survey in the United Kingdom (Kelly et al, 2001;O'Sullivan et al, 2011) and the National Health and Nutrition Examination Surveys in the United States (Dye et al, 2007;Dye et al, 2008;Dye et al, 2011), have measured attachment loss (AL) in addition to PD.…”
mentioning
confidence: 99%